Energetic Interactions Between Subcellular Organelles in Striated Muscles - Piquereau, Jérôme; Veksler, Vladimir; Novotova, Marta; Ventura-Clapier, Renée (Frontiers in Cell and Developmental Biology, 2020)
Adult striated muscle cells present highly organized structure with densely packed intracellular organelles and a very sparse cytosol accounting for only few percent of cell volume. These cells have a high and fluctuating energy demand that, in continuously working oxidative muscles, is fulfilled mainly by oxidative metabolism. ATP produced by mitochondria should be directed to the main energy consumers, ATPases of the excitation-contraction system; at the same time, ADP near ATPases should rapidly be eliminated. This is achieved by phosphotransfer kinases, the most important being creatine kinase (CK). Specific CK isoenzymes are located in mitochondria and in close proximity to ATPases, forming efficient energy shuttle between these structures. In addition to phosphotransfer kinases, ATP/ADP can be directly channeled between mitochondria co-localized with ATPases in a process called “direct adenine nucleotide channeling, DANC”. This process is highly plastic so that inactivation of the CK system increases the participation of DANC to energy supply owing to the rearrangement of cell structure. The machinery for DANC is built during postnatal development in parallel with the increase in mitochondrial mass, organization and complexification of the cell structure. Disorganization of cell architecture remodels the mitochondrial network and decreases the efficacy of DANC, showing that this process is intimately linked to cardiomyocyte structure. Accordingly, in heart failure, disorganization of the cell structure along with decrease in mitochondrial mass reduces the efficacy of DANC and together with alteration of the CK shuttle participates in energetic deficiency contributing to contractile failure.